The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

The Cd(II)-binding abilities of recombinant Quercus suber metallothionein: bridging the gap between phytochelatins and metallothioneins. - Domenech, Jordi; Orihuela, Ruben; Mir, Gisela; Molinas, Marisa; Atrian, Silvia; Capdevila, Merce (Journal of biological inorganic chemistry : JBIC : a publication of the Society of Biological Inorganic Chemistry, 2007)
In this work, we have analyzed both at stoichiometric and at conformational level the Cd(II)-binding features of a type 2 plant metallothionein (MT) (the cork oak, Quercus suber, QsMT). To this end four peptides, the wild-type QsMT and three constructs previously engineered to characterize its Zn(II)- and Cu(I)-binding behaviour, were heterologously produced in Escherichia coli cultures supplemented with Cd(II), and the corresponding complexes were purified up to homogeneity. The Cd(II)-binding ability of these recombinant peptides was determined through the chemical, spectroscopic and spectrometric characterization of the recovered clusters. Recombinant synthesis of the four QsMT peptides in cadmium-rich media rendered complexes with a higher metal content than those obtained from zinc-supplemented cultures and, consequently, the recovered Cd(II) species are nonisostructural to those of Zn(II). Also of interest is the fact that three out of the four peptides yielded recombinant preparations that included S(2-)-containing Cd(II) complexes as major species. Subsequently, the in vitro Zn(II)/Cd(II) replacement reactions were studied, as well as the in vitro acid denaturation and S(2-) renaturation reactions. Finally, the capacity of the four peptides for preventing cadmium deleterious effects in yeast cells was tested through complementation assays. Consideration of all the results enables us to suggest a hairpin folding model for this typical type 2 plant Cd(II)-MT complex, as well as a nonnegligible role of the spacer in the detoxification function of QsMT towards cadmium.
The following values have no corresponding Zotero field: accession-num: 17503092
Keywords: cadmium; Cadmium: chemistry; Cadmium–His binding; Drug; Glutathione; Metabolic Detoxication; metallothionein; Metallothionein: chemistry; Metallothionein: metabolism; Phytochelatins; Plant metallothionein; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Protein Binding; Protein Conformation; Quercus; Recombinant Proteins; Sulfide ligands; yeast complementation

Plant metallothionein domains: functional insight into physiological metal binding and protein folding - Domenech, Jordi; Mir, Gisela; Huguet, Gemma; Capdevila, Merce; Molinas, Marisa; Atrian, Silvia (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.
Keywords: Cu-aggregates; metallothionein; MT dimers; Quercus suber; separate Cys-rich domains; spacer region; yeast complementation; Zn-aggregates

Plant metallothionein domains: functional insight into physiological metal binding and protein folding - Domenech, Jordi; Mir, Gisela; Huguet, Gemma; Capdevila, Merce; Molinas, Marisa; Atrian, Silvia (BIOCHIMIE, 2006)
Plant metallothioneins (MTs) differ from animal MTs by a peculiar sequence organization consisting of two short cysteine-rich terminal domains linked by a long cysteine-devoid spacer. The role of the plant NIT domains in the protein structure and functionality is largely unknown. Here, we investigate the separate domain contribution to the in vivo binding of Zn and Cu and to confer metal tolerance to CUP1-null yeast cells of a plant type 2 NIT (QsMT). For this purpose, we obtained three recombinant peptides that, respectively, correspond to the single N-terminal (N25) and C-terminal (C18) cysteine-rich domains of QsMT, and a chimera in which the spacer is replaced with a four-glycine bridge (N25-C18). The metal-peptide preparations recovered from Zn- or Cu-enriched cultures were characterized by ESI-MS, ICP-OES and CD and UV-vis spectroscopy and data compared to full length QsMT. Results are consistent with QsMT giving rise to homometallic Zn- or Cu-MT complexes according to a hairpin model in which the two Cys-rich domains interact to form a cluster. In this model the spacer region does not contribute to the metal coordination. However, our data from Zn-QsMT (but not from Cu-QsMT) support a fold of the spacer involving some interaction with the metal core. On the other hand, results from functional complementation assays in endogenous MT-defective yeast cells suggest that the spacer region may play a role in Cu-QsMT stability or subcellular localization. As a whole, our results provide the first insight into the structure/function relationship of plant MTs using the analysis of the separate domain abilities to bind physiological metals. (c) 2005 Elsevier SAS. All rights reserved.
The following values have no corresponding Zotero field: pub-location: 23 RUE LINOIS, 75724 PARIS, FRANCE publisher: ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER
Keywords: Cu-aggregates; metallothionein; MT dimers; Quercus suber; separate Cys-rich domains; spacer region; yeast complementation; Zn-aggregates

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber

Influence of weather on cork-ring width - Caritat, Antònia; Gutiérrez, Emilia; Molinas, Marisa (Tree Physiology, 2000)
Ring-width series of cork from Quercus suber L. trees growing at two sites in Extremadura (southwestern Spain) were analyzed in relation to monthly precipitation and temperature, and to climatic indices combining both variables. Ring width of cork showed strong positive correlations with precipitation, especially during the fall and winter. Moderately low temperatures were favorable for cork growth, except in winter and during the onset of phellogen activity. We conclude that drought or temperature, or both, can limit cork growth during the annual drought period.
10.1093/treephys/20.13.89310.1093/treephys/20.13.893
Keywords: climatic variability; cork growth; cork-ring chro- nology; dendroclimatology; phellogen activity; Quercus suber

Developmental anatomy and apical organization of the primary root of cork oak (Quercus auber L. - Verdaguer, Dolors; Molinas, Marisa (International Journal of Plant Sciences, 1999)
Using histological techniques, we investigated the development and organization of the primary root and the root apex of Quercus suber L. (cork oak), a Mediterranean woody species growing in semiarid conditions. The presence of a quiescent center was also investigated. The histogenesis of the vascular system begins with the maturation of the protophloem elements. Primary phloem and xylem strands form alternately, and maturation proceeds centripetally, although xylem differentiation does not reach the center of the root, which is occupied by a pith. Most protoxylem elements were fully mature well before the endodermis entered State I with the formation of the Casparian strip. A continuous vascular cambium forms before the initiation of the phellogen in the outermost pericyclic layer. In the primary root the apex has an open organization with four groups of initials: vascular cylinder initials, cortical initials, lateral root-cap initials, and columella initials. The quiescent center includes the vascular initials and some derivatives. These features contrast with the radicle in mature and germinating embryos that have a closed organization with three groups of initials and a wider quiescent center.
Keywords: development; meristem; primary root; Quercus suber; quiescent center; vascular development

Stress proteins co-expressed in suberized and lignified cells and in apical meristems - Pla, Maria; Huguet, Gemma; Verdaguer, Dolors; Puigderrajols, Pere; Llompart, Blanca; Nadal, Anna; Molinas, Marisa (Plant Science, 1998)
We report the cloning of a small heat shock protein, Qs –HSP17, and an osmotin like protein, Qs –OLP, from cork oak phellem tissue (cork cells). Both genes are expressed in suberizing cells and in other cells subject to endogenous stress associated with free radicals. We provide evidence that smHSPs and OLPs accumulate in overwintering buds and speculate that their role is similar to that in seed dormancy. We also show that both stress proteins are mainly located in the region of the quiescent center in root apex and in central meristem in the shoot apex. We emphasize that smHSPs and OLPs are expressed in cells growing under endogenous stress or facing long life-span. We discuss a possible role of these stress proteins against oxidative stress
Keywords: cork-oak; osmotin like proteins; phellem; Quercus suber; small heat shock proteins; tissue specificity

Development and ultrastructure of the endodermis in the primary root of cork oak (Quercus suber) - Verdaguer, Dolors; Molinas, Marisa (Canadian Journal of Botany, 1997)
The endodermis maturation process was studied in the primary root of the cork oak (Quercus suber L.) with emphasis on the chemical nature of the cell wall and on the possible role of tannins. Tannins were found in endodermal and adjacent cortical cells in all maturation stages. We discuss our findings in relation to the previous literature in other woody and herbaceous species. The results of the histochemical tests showed differences in the aliphatic compounds of the suberin between the Casparian strip suberin and the suberin layer deposited in state II cells. Plasmodesmata were present in radial and tangential walls during the entire maturation process. The significance of plasmodesmata and of the suberin deposition pattern is discussed in relation to apoplastic and symplastic transport in roots. Key words: Casparian strip, endodermis, primary root, suberin, Quercus suber L.
doi: 10.1139/b97-087
Keywords: Casparian strip; endoderrnis; primary root; Quercus suber L.; suberin